Management of COVID-19 in Universitas Gadjah Mada (UGM) Academic Hospital: Balancing to save the patients and protect the staffs - Siswanto, Siswanto; Utama, Oktaviarum Slamet; Sari, Astari Pranindya; Alfajri, Novi Zain; Lestari, Ade Febrina (Rumah Sakit Akademik Universitas Gadjah Mada, 2023)
The Coronavirus Disease 2019 (COVID-19) is a worldwide outbreak disease caused by Severe Acute Respiratory Syndrome Coronavirus-2 (SARS-CoV-2). Indonesia is the fourth most populous country in the world and is predicted to be affected significantly over a more extended period. Universitas Gadjah Mada (UGM) Academic Hospital is one of the COVID-19 referral hospitals located in the Yogyakarta Special Region, Indonesia. Since the early months of the pandemic, the hospital has prepared strategies to provide effective and efficient patient care. The focus has been safety for both patients and healthcare staff. Here, we will share our experiences activating a Hospital Incident Command System (HICS) as a hallmark for preparedness and response to the COVID-19 pandemic disaster so it can be adopted in other hospitals nationwide or worldwide. The HICS in the UGM Academic Hospital includes 1) surge capacity for isolation rooms, 2) infection prevention and control, 3) human resources, 4) continuity of essential health services and patient care, 5) communication, 6) logistics and management of supplies including pharmaceuticals, 7) essential support services, 8) case management system, 9) surveillance early warning and monitoring, 10) laboratory services, and 11) additional programs including community service programs. Based on our experiences, early preparedness with a proactive response, and adapting plans to local needs, the national and global current situation are the keys to managing patient care. Implementing all levels of the hierarchy of control infection and keeping the human resources adequate also could protect staff